Activin A regulates activation of mouse neutrophils by Smad3 signalling - Yan Qi; Jingyan Ge; Chunhui Ma; Na Wu; Xueling Cui; Zhonghui Liu (Open Biology, 2017)
Activin A, a member of the transforming growth factor beta superfamily, acts as a pro-inflammatory factor in acute phase response, and influences the pathological progress of neutrophil-mediated disease. However, whether activin A can exert an effect on the activities of neutrophils remains unclear. In this study, we found that the release of activin A was enhanced from neutrophils of mouse when stimulated with lipopolysaccharide. Furthermore, neutrophils were not only the source of activin A but also the target cells in response to activin A, in which canonical activin signalling components existed, and levels of ACTRIIA, SMAD3 and p-SMAD3 proteins were elevated in activin A-treated neutrophils. Next, the role of activin A was determined in regulation of neutrophils activities. Our data revealed that activin A induced O2− release and reactive oxygen species production, promoted IL-6 release, and enhanced phagocytosis, but failed to attract neutrophils migrating across the trans-well membrane. Moreover, we found that effect of activin A on IL-6 release from the peritoneal neutrophils of mouse was significantly attenuated by in vivo Smad3 knockdown. In summary, these data demonstrate that activin A can exert an effect on neutrophils activation in an autocrine/paracrine manner through Smad3 signalling, suggesting that activin A is an important regulator of neutrophils.